Institutional herding in international markets - Choi, Nicole; Skiba, Hilla (Journal of Banking & Finance, 2015)
This paper studies herding behavior of institutional investors in international markets. First, we document the existence of wide-spread herding in 41 countries (referred to as “target countries” hereafter) in the sample. We then examine the relation between contemporaneous institutional demand and future returns and find that institutional herding stabilizes prices. Next, we examine the relation between institutional investors’ herding behavior and the level of information asymmetry in the target countries. We measure the degree of information asymmetry in each target country along five dimensions: (1) stock market development, (2) ease of access to information, (3) corporate transparency, (4) investor rights, and (5) macroeconomic factors that relate to the information environment. We find evidence that institutional investors herd more in markets characterized by low levels of information asymmetry (high level of information transparency). This result suggests that institutional investors’ herding behavior is likely driven by correlated signals from fundamental information. Lastly, we show that price adjustment is faster in informationally transparent markets.